Persistence of exponential decay and spectral gaps for interacting fermions - De Roeck, Wojciech; Salmhofer, Manfred (Communications in mathematical physics, 2019)
We consider systems of weakly interacting fermions on a lattice. The corresponding free fermionic system is assumed to have a ground state separated by a gap from the rest of the spectrum. We prove that, if both the interaction and the free Hamiltonian are sums of sufficiently rapidly decaying terms, and if the interaction is sufficiently weak, then the interacting system has a spectral gap as well, uniformly in the lattice size. Our approach relies on convergent fermionic perturbation theory, thus providing an alternative method to the one used recently by Hastings (The stability of free Fermi hamiltonians, arXiv:1706.02270, 2017), and extending the result to include non-selfadjoint interaction terms.
Published online: 23 July 2018
Gesehen am 27.11.2020